A budapesti zsidó lakosság gazdasági szerepe 1873–1918 között - Leba, József (Közép-Európai Közlemények, 2024)
The Hungarian capital, established in 1873, began to develop rapidly almost immediately. The XX. by the beginning of the century, Budapest had developed into a real world city. The citizens of the big city participated in this development in various ways. Not only Hungarians, but also many other nationalities settled in Budapest. Among these nationalities, I analyze the Jews. First, I will introduce their first residence, the Orczy House. At that time, they could not live within the city walls. In the second chapter, I briefly analyze the Jewish population of Terézváros, Erzsébetváros and Józsefváros. Then I turn to the analysis of the Jewish population of Budapest according to income and professions, starting from the top layer and moving downwards. In my study, I explain that they were most present in trade, banking and in the entrepreneurial sector in general. They were also attracted to independent intellectual careers. In Budapest, neologism and orthodox tendencies were present, whose, mentality, customs and attitude towards the majority society differed somewhat.